Neural Kinesthetic Contribution to Motor Imagery of Body Parts: Tongue, Hands, and Feet - Giannopulu, Irini; Mizutani, Haruo (Frontiers in Human Neuroscience, 2021)
Motor imagery is assimilated to a perception-action process, which is mentally represented. Although several models suggest that motor imagery, and its equivalent motor execution, engage very similar brain areas, the mechanisms underlying motor imagery and their associated components are still under investigation today. Using twenty-two Ag/AgCl EEG electrodes, 19 healthy participants (9 males and 10 females) with an average age of 25.8 years old (sd=3.5 years) were required to imagine moving several parts of their body (i.e. first person perspective) one by one: left and right hand, tongue and feet. Network connectivity analysis based on graph theory, together with a correlational analysis, were performed on the data. The findings suggest evidence for motor and somesthetic neural synchronisation and underline the role of the parieto-frontal network for the tongue imagery task only. At both unilateral and bilateral cortical levels, only the tongue imagery task appears to be associated with motor and somatosensory representations, that is, kinaesthetic representations, which might contribute to verbal actions. As such, the present findings suggest the idea that imagined tongue movements, involving segmentary kinaesthetic actions, could be the prerequisite of language.